Die Mär vom griechischen und/oder wölfischen Ursprung von Lykiern, Lykaonen, Lukkā und Luwija - Schürr, Diether (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The Greek name for the Trm͂mili people in Asia Minor was Λύκιοι, naturally explained by some Greek authors as from λύκος, ‘wolf’, either directly or via a personal name. This has inspired modern explanations by means of the same word. The first was that the Hittite country of Luwija was, just like Lycia, named after wolves, i.e. from a word for ‘wolf’ cognate with the Greek word, whereas the Akkadian name-form Lukku of another country have been influenced by the Greek form. The second explanation was that the Lycians, the Lycaonians and even the Hittite land of Lukkā were named after λύκος, but that this would be a word of pre-Greek origin. The third retains λύκος as a Greek word, making out that Lycians and Lycaonians, together with Lukkā, were originally Greek worshippers of a wolfish Apollo. The fourth turns the Lycians – and then also Lukkā – in the wake of the racist ‘Männerbund’ ideology, into a wolfish Greek ‘Jungmannschaft’, which became the ruling class in the later Lycia. This is certainly a fantasy without any linguistic or archaeological basis, and the explanation of Lukkā via a non-Greek but Proto-Anatolian *lukos ‛wolf’ is not a viable alternative. And there is no need to explain the name of the Bronze Age land of Luwiya via a putative Proto-Indo-European *lukwos either. Lukkā, Lykioi and Lykaones are more plausibly derived from the PIE root *leuk-/louk-/luk-, like English light. An independent attempt, which depicts the Lycians as former Aegean migrants who abandoned their Greek language, is based on two Greek loanwords, a putative link between a Lycian and a Greek word, and two phonological developments which have parallels in Greek, but are of a very different age. This is certainly not enough to corroborate that hypothesis.